Do larger reductions yield larger returns? patient-reported outcomes as a function of specimen weight in bilateral reduction mammoplasty. Issue 10 (October 2021) - Yao, Amy; LaFontaine, Samantha; Sultan, Steven M.; Rizzo, Amanda M.; Draper, Lawrence; Benacquista, Teresa; Weichman, Katie E.
Abstract: Background: Patients undergoing breast reduction mammoplasty for symptomatic macromastia have a significantly improved quality of life postoperatively. However, there are no data that examine the effect of reduction mammoplasty on quality of life as a function of the weight of tissue removed. Because the process by which insurance providers consider patients' candidacy for this breast reduction mammoplasty is most often based on the proposed weight of tissue to be removed, this gap in our understanding is particularly glaring. We therefore designed a prospective trial with the intent of investigating the correlation between breast reduction specimen weight and postoperative pain and quality of life. Methods: After obtaining institutional review board (IRB) approval, patients presenting for breast reduction mammoplasty at a single academic medical center between January 2016 and September 2019 were prospectively enrolled in the study. Study participants completed the Numerical Pain Rating Scale (NPRS), the short-form McGill Pain Questionnaire (SF-MPQ), and the BREAST-Q at set time points (preoperatively, 1 week/1 month/3 months/6 months postoperatively). Patients were divided into three cohorts based on breast reduction specimen weights: small (<500 g reduction), intermediate (500–1000 g reduction), and large (>1000 g reduction). The surveys were then analyzed while controlling for demographic factors and complications. Results: A total of 85 women were enrolled in the study and completed pre- and postoperative surveys (small reduction n  = 21 (25%), intermediate n  = 45 (53%), and large n  = 19 (22%)). Regardless of reduction specimen weight, patients reported decreased overall pain and increased satisfaction with their breasts, as well as improved psychosocial, sexual, and physical well-being at each postoperative visit. Preoperative SF-MPQ pain scores were significantly lower in the small specimen weight group compared with either the intermediate or the large group ( p  = 0.001). Postoperatively, both the intermediate and large groups reported significant improvement in pain at each time point. The small specimen weight group did not report significant pain improvement until 3 months postoperatively. Conclusions: Patients undergoing breast reduction mammoplasty experience decreased pain and improved quality of life regardless of reduction specimen weight. Improvement in these parameters manifests as early as 1 week postoperatively and maintained at 3 months postoperatively. These data suggest that many patients who are denied coverage for reduction mammoplasty on the basis of low projected reduction specimen weight would derive significant benefit from the procedure.